Work Ethic and Employee Performance: The Mediating Role of Innovative Work Behavior and the Moderating Role of Organizational Citizenship Behavior - Savira Erens Rahmadina; Adya Hermawati; Survival Survival (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of work ethic on employee performance by including innovative work behavior as a mediating variable and organizational citizenship behavior (OCB) as a moderating variable. The study was conducted on Civil Servants at the Batu City Agriculture and Food Security Office using a quantitative explanatory approach. The entire population of 83 employees was used as respondents through a saturated sampling technique, so this study is expected to be able to describe the empirical conditions comprehensively. Quantitative data were collected through distributing questionnaires compiled based on research variable indicators and then analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of SmartPLS software version 4. The results of the analysis indicate that work ethic has a positive and significant influence on employee performance. In addition, work ethic is also proven to have a positive and significant influence on innovative work behavior. Further findings indicate that innovative work behavior acts as a partial mediating variable in the relationship between work ethic and employee performance, meaning that work ethic can improve performance both directly and through increasing innovative behavior. However, organizational citizenship behavior (OCB) is not proven to moderate the relationship between work ethic and employee performance. This indicates that the role of OCB in strengthening or weakening the influence of work ethic on performance is not yet significant in the context of the organization studied.